Effect on the mechanical properties of human and bovine dentine of intracanal medicaments and irrigants. (16th October 2018) - Cochrane, S; Burrow, MF; Parashos, P
Abstract: Background: Evidence is lacking concerning the suitability of using bovine dentine in endodontic research. This study compared the mechanical properties of human and bovine root dentine using endodontic medicaments and irrigants. Methods: Standardized human and bovine dentine bars were allocated to six experimental groups (n = 15): calcium hydroxide paste (Calasept ® Plus); Odontopaste ® ; 0.5% and 1% NaOCl gels; 1% and 4% NaOCl solutions. The bars were exposed to the materials for 7 days and then immediately subjected to a three‐point bend test and Vickers microhardness test. Data were analysed using analysis of variance with Fisher's pairwise comparisons, with P < 0.05. Results: Human dentine displayed a significantly higher modulus of elasticity ( P = 0.001), higher microhardness ( P < 0.001), and lower flexural strength ( P = 0.004) compared with bovine dentine. Calcium hydroxide and Odontopaste ® did not result in a significant change to the mechanical properties of human dentine. In human dentine, 0.5% NaOCl gel caused a significant decrease in flexural strength ( P < 0.001) and microhardness ( P = 0.02). Conclusions: Bovine dentine was a suitable substrate relative to human dentine. The use of a 0.5% or 1% NaOCl gel as an intracanal medicament is not supported by this study.